Optimizing nursing care for neutropenic patients: a holistic perspective on education, support, and clinical management - Xu, Zhao-ning; Gao, Li-ping; Wang, Xin-kai; Yu, Xiu-li; Cong, Yue; Wang, Peng-ju (Frontiers in Medicine, 2025)
Neutropenia, characterized by neutrophil counts below 1,500 cells/μL, increases infection risk and worsens treatment outcomes in oncology and immunocompromised patients. This paper outlines evidence-based nursing strategies in four domains: (1) Clinical management with strict infection control, risk tools, and targeted drug therapies; (2) Patient education through competency-based training and mHealth tools, improving adherence by 42%; (3) Psychosocial support using telehealth and model of Managing Cancer And Living Meaningfully therapy, reducing distress by 38–45%; and (4) Interdisciplinary care with structured pathways lowering complications by 25–30%. Challenges include 40% non-adherence, rural care gaps, and inconsistent protocols. Future strategies include telemedicine (45% adherence gain), genetic risk tools, and machine learning for early detection.